Successful correction of hemophilia by CRISPR/Cas9 genome editing in vivo: delivery vector and immune responses are the key to success - Tuan Huy Nguyen; Ignacio Anegon (EMBO Molecular Medicine)
Abstract Hemophilia B is a serious hemostasis disorder due to mutations of the factor IX gene in the X chromosome. Gene therapy has gained momentum in recent years as a therapeutic option for hemophilia B. In hemophilia, reconstitution with a mere 1–2% of the clotting factor improves the quality of life, while 5–20% suffices to ameliorate the bleeding disorder. A paper by Guan et al (2016) in this issue of EMBO Molecular Medicine reports on the direct CRISPRs/Cas9‐mediated correction in the liver of a hemophilia‐causing point mutation in FIX.